‫تأثير ‬الإعلان‬ ‫على‬ ‫سلوك‬ ‫المستهلك‬ ‫بوكالة‬ ‫تويوتا‬ ‫سوق‬ ‫أهراس‬ - ‬‫نادية ‫سديرة ‬; ‬‫كريمة ‫قوادرية ‬ (My University, 2017)
The main objective of studying this topic is to provide a theoretical framework identifies and defines the different concepts relating to advertising and consumer behavior, it has been identified as the various internal and external factors that affect it. Additionally in the field study, it looks at the impact of the Toyota advertising agency on the behavior of consumers of souk_ahras. Where he was identified on the consumer information, as well as knowledge of his interaction with her, in addition to standing on the measure of consumer affected by depending on the characteristics personal, and the degree of consumer reaction to the agency Toyota advertising vary depending on the advertising method used by, while like television the most important means used to follow the agency's announcements.